The complete adventures of Charlie and Mr Willy Wonka - Dahl, Roald (Puffin, 2016)
Charlie can't believe his luck when he wins one of the five places on a tour around Willy Wonka's famous chocolate factory. He sees the creation of the most delicious eatables in the world.The excitement continues as Charlie and his family zoom into the stratosphere in Mr Wonka's glass elevator. Unfortunately, before they know it, they can't get back down to Earth!Two of Roald Dahl's best-loved stories in one volume.